Orthogonal coiled coils enable rapid covalent labelling of two distinct membrane proteins with peptide nucleic acid barcodes. Issue 4 (22nd July 2021) - Gavins, Georgina C.; Gröger, Katharina; Reimann, Marc; Bartoschek, Michael D.; Bultmann, Sebastian; Seitz, Oliver
Abstract : A pair of orthogonal coiled coils templates highly specific live cell bioconjugation of two different proteins. PNA tagging and hybridisation with fluorophore–DNA reporters enables rapid dual receptor internalisation analysis of EGFR and ErbB2. Abstract : Templated chemistry offers the prospect of addressing specificity challenges occurring in bioconjugation reactions. Here, we show two peptide-templated amide-bond forming reactions that enable the concurrent labelling of two different membrane proteins with two different peptide nucleic acid (PNA ) barcodes. The reaction system is based on the mutually selective coiled coil interaction between two thioester-linked PNA –peptide conjugates and two cysteine peptides serving as genetically encoded peptide tags. Orthogonal coiled coil templated covalent labelling is highly specific, quantitative and proceeds within a minute. To demonstrate the usefulness, we evaluated receptor internalisation of two membranous receptors EGFR (epidermal growth factor) and ErbB2 (epidermal growth factor receptor 2) by first staining PNA -tagged proteins with fluorophore–DNA conjugates and then erasing signals from non-internalized receptors via toehold-mediated strand displacement.